Nano-cracks in a synthetic graphite composite for nuclear applications. Issue 14 (13th May 2018) - Liu, Dong; Cherns, David
Abstract: Mrozowski nano-cracks in nuclear graphite were studied by transmission electron microscopy and selected area diffraction. The material consisted of single crystal platelets typically 1–2 nm thick and stacked with large relative rotations around the c -axis; individual platelets had both hexagonal and cubic stacking order. The lattice spacing of the (0002) planes was about 3% larger at the platelet boundaries which were the source of a high fraction of the nano-cracks. Tilting experiments demonstrated that these cracks were empty, and not, as often suggested, filled by amorphous material. In addition to conventional Mrozowski cracks, a new type of nano-crack is reported, which originates from the termination of a graphite platelet due to crystallographic requirements. Both types are crucial to understanding the evolution of macro-scale graphite properties with neutron irradiation.